Satisfaction with the use of metal brackets in relation to oral hygiene, comfort and esthetic self-perception - Paulina Gacitúa; Fabiola Andrea Werlinger; Matías Ríos; Eduardo Alvarez (Editorial Ciencias Médicas, 2015)
Introduction: although brackets are intended to improve dental esthetics, they are also associated with negative reactions, due to the need to use visible fixed appliances altering the patient's physiognomy, functional capacity and oral hygiene. This could lead to low adherence to orthodontic treatment. Objective: evaluate patient satisfaction with metal brackets in relation to oral hygiene, comfort and esthetic self-perception in the first and fourth weeks of treatment. Methods: an longitudinal prospective observational study was conducted on an individual basis. Starting from the judgment of three experts, an orthodontic treatment satisfaction questionnaire was developed based on 10 questions about the variables oral hygiene, comfort and esthetic self-perception. From the universe of patients about to start treatment at the National Institute of Orthodontics in Santiago de Chile, a sample of 45 individuals was selected applying the antecedents described by Caniklioglu. Participants were selected by convenience between May and June 2012. All male and female patients aged over 15 years were included, except for those who had undergone previous orthodontic treatment or suffered from conditions preventing them from answering the questionnaire. Results: final reliability of the questionnaire was α= 0.769. Score variation between the first and the second measurement was 8.06 ± 1.65 to 10.82 ± 1.52 points for oral hygiene, 10.51 ± 2.2 to 15.42 ± 1.97 points for comfort and 8.64 ± 1.83 to 11.37 ± 1.64 points for esthetic self-perception. Total score was 27.2 ± 4.48 points for the first week of treatment and 37.6 ± 4.02 points for the fourth week. Conclusions: overall satisfaction among Chilean patients wearing metal brackets improves from the first to the fourth week after installation of the appliance. This applies to all three dimensions: oral hygiene, comfort and esthetic self-perception.